First record of Ceriporia inflata and Ceriporia lacerata (Phanerochaetaceae, Basidiomycota) from Indonesian tropical forest - Wulandari, Retno; Lotrakul, Pongtharin; Amirta, Rudianto; Kim, Seung Wook; Punnapayak, Hunsa; Prasongsuk, Sehanat (Agriculture and Natural Resources, 2018)
Resupinate fungi (Basidiomycota) are wood-inhabiting fungi found abundantly in the tropical rainforest of Indonesia. A survey in East Kalimantan discovered two new recorded species for Indonesia: Ceriporia inflata and Ceriporia lacerata. The morphological characteristics of these two resupinate fungi were similar to those of the holotype specimens found in sub-tropical forest in China and Japan. Based on maximum parsimony and Bayesian phylogenetic analysis of internal transcribed spacers and large subunit nuclear ribosomal RNA sequences, these two new records were placed within the Ceriporia group.